Reconstruction of Beef Cattle and Dairy Cattle Development in Indonesia - Siregar, Abdulrahman; Karto, Abdurrays Ambar (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Dairy cattle and beef cattle industrial development have not fulfilled consumption requirement in Indonesia. Indonesia has imported milk since the beginning of Pelita I (Five years planning of Indonesian development). Once Indonesia was able to export beef, but a now days beefis being imported, and continue to increase every year. There are four factors need to be considered (1) the dairy and beef cattle form which has been raised separately, should be raised jointly and developed with "dual purpose" cattle, (2) livestock production system, should be carried as commercial enterprise, (3) application of appropriate technologies, (4) develop proper marketing in line with production system. Key words : Dairy cattle, beef cattle, "dual purpose" cattle, milk, meat, development